Léčba hypertenze snižuje riziko srdečního selhání a cévních mozkových příhod i u starších pacientů - Beckett NS, N. S; Peters, R; Fletcher, A. E (Postgraduální nefrologie, 2008)
Whether the treatment of patients with hypertension who are 80 years of age or older is beneficial is unclear. It has been suggested that antihypertensive therapy may reduce the risk of stroke, despite possibly increasing the risk of death. METHODS: We randomly assigned 3845 patients from Europe, China, Australasia, and Tunisia who were 80 years of age or older and had a sustained systolic blood pressure of 160 mm Hg or more to receive either the diuretic indapamide (sustained release, 1.5 mg) or matching placebo. The angiotensin-converting-enzyme inhibitor perindopril (2 or 4 mg), or matching placebo, was added if necessary to achieve the target blood pressure of 150/80 mm Hg. The primary end point was fatal or nonfatal stroke. RESULTS: The active-treatment group (1933 patients) and the placebo group (1912 patients) were well matched (mean age, 83.6 years; mean blood pressure while sitting, 173.0/90.8 mm Hg); 11.8% had a history of cardiovascular disease. Median follow-up was 1.8 years. At 2 years, the mean blood pressure while sitting was 15.0/6.1 mm Hg lower in the active-treatment group than in the placebo group. In an intention-to-treat analysis, active treatment was associated with a 30% reduction in the rate of fatal or nonfatal stroke (95% confidence interval [CI], -1 to 51; P=0.06), a 39% reduction in the rate of death from stroke (95% CI, 1 to 62; P=0.05), a 21% reduction in the rate of death from any cause (95% CI, 4 to 35; P=0.02), a 23% reduction in the rate of death from cardiovascular causes (95% CI, -1 to 40; P=0.06), and a 64% reduction in the rate of heart failure (95% CI, 42 to 78; P<0.001). Fewer serious adverse events were reported in the active-treatment group (358, vs. 448 in the placebo group; P=0.001). CONCLUSIONS: The results provide evidence that antihypertensive treatment with indapamide (sustained release), with or without perindopril, in persons 80 years of age or older is beneficial. (ClinicalTrials.gov number, NCT00122811 [ClinicalTrials.gov].). Copyright 2008 Massachusetts Medical Society.
Keywords: kombinovaná farmakoterapie; Antihypertensive Agents; senioři nad 80 let; krevní tlak; Humans; diuretika; lidé; hypertenze; Aged, 80 and over; Angiotensin-Converting Enzyme Inhibitors; kardiovaskulární nemoci; Hypertension; indapamid; Perindopril; antihypertenziva; Female; Double-Blind Method; Diuretics; Stroke; Male; Kaplan-Meier Estimate; Blood Pressure; následné studie; Follow-Up Studies; dvojitá slepá metoda; cévní mozková příhoda; Cardiovascular Diseases; Drug Therapy, Combination; Indapamide; ženské pohlaví; mužské pohlaví; inhibitory ACE; Kaplanův-Meierův odhad; perindopril